Upaya Peningkatan Harga Diri Rendah Dengan Terapi Aktivitas Kelompok (Stimulasi Persepsi) di Ruang Asoka (Sub Akut Laki) RSKD Provinsi Maluku - Tuasikal, Hani; Siauta, Moomina; Embuai, Selpina (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Low self-esteem is a condition where an individual experiences negative self-evaluation of his abilities. Giving TAK effective stimulation of perception supported by the environment where the therapy is given, and willingness to participate in activities, it is expected to overcome low self-esteem can also perceive what is described properly and appropriate. Purpose: to apply mental nursing care to tn. y with low self-esteem in an effort to increase self-esteem with group activity therapy. Research methods: descriptive research methods with case studies. Research Results: Based on the results of the study, there was no gap between the theory and the results of the study. Conclusion: Group Activity Therapy (Stimulation of Perception) can increase the client's self-esteem.